Poznanie poza językiem. Przypadek religijnego doświadczenia mistycznego a jego wysłowienie - Sakaguchi, Alicja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
An analysis of the experiences, insights and proclamations by mystics and prophets from various epochs unveils the characteristics of individuals exposed to long experiences and holistic (or integral) cognition. A mystic transformation affects the mode of speaking and communicating with the world. Language with its stereotypical phrases and connotations certainly limits human cognition. However, in the process of their transpersonal experience, mystics go beyond this barrier and overcome cognitive limitations including the flaws of human language. In order to present an altogether “different” space of reality shared by mystics, and to share their proclamations and teaching with a large audience, mystics apply very specific linguistic tools like the metaphor, allegory, antithesis, paradox, analogy, symbol, quotations from the Bible, hyperbole, parallelism, chiasm and, last but not least, parable. An act of viewing the prophecy and epiphany-related language reflecting the authors’ synoptic (mystic) awareness “from the inside” makes it possible to identify archetypal criteria of the mystic experience and to establish the correct meaning of the key expressions (the sacred) and sacral acts of speech.